2020
DOI: 10.46328/ijres.1786
|View full text |Cite
|
Sign up to set email alerts
|

“Not Just For Us Nerds”: Examining Elementary Teachers’ Perspectives of Contemporary Children’s Nonfiction

Abstract: Children’s nonfiction once had a reputation as a lackluster genre. However, the nonfiction books published today are noteworthy for their appeal and quality. This study’s purpose was to examine contemporary teachers’ perceptions of recent children’s nonfiction. Fourteen elementary teachers shared their opinions of contemporary nonfiction for children in written reflections, which were inductively analyzed using qualitative content analysis. The teachers addressed the following themes in their reflections: 1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…The inclination toward traditional models from their primary education seems to prevail, rather than fully incorporating the knowledge gained during their university training into their prospective teaching approaches. Consequently, it is pertinent to propose that university training endeavors to reconstruct the pre-existing belief systems of teachers, considering the pedagogical advantages of these materials widely acknowledged by researchers, as indicated by Hartsfield (2021) and Romero et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclination toward traditional models from their primary education seems to prevail, rather than fully incorporating the knowledge gained during their university training into their prospective teaching approaches. Consequently, it is pertinent to propose that university training endeavors to reconstruct the pre-existing belief systems of teachers, considering the pedagogical advantages of these materials widely acknowledged by researchers, as indicated by Hartsfield (2021) and Romero et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, there is an emphasis on the significance of teachers cultivating confidence in the selection and integration of these materials into their educational settings. Furthermore, the continuation of postgraduate education among active teachers is recommended, involving ongoing training courses that incorporate nonfiction picturebooks (Hartsfield, 2021). This educational approach aims to empower teachers to apply their acquired knowledge consistently in their classrooms, effectively mitigating the existing imbalance between the prevalence of fiction and nonfiction readings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, studies such as that of Hartsfield (2021) and Romero, Trigo & Heredia (2021) focus on the place of the mediator in the reading of children's nonfiction books, analyzing their beliefs and attitudes with practicing teachers (Hartsfield, 2021;Romero, Trigo & Heredia, 2021) and teachers in training (Romero, Trigo & Heredia, 2021). As the main finding of these qualitative studies, the participants found numerous advantages derived from reading nonfiction books in the classroom: positive opinions on the part of teachers about the new nonfiction books, the possibility of shared teacher-student reading, and their usefulness in both linguistic and non-linguistic areas.…”
Section: Empirical Studies On the Reading Of Children's Nonfiction Pi...mentioning
confidence: 99%